Genetic and molecular pathways controlling rice inflorescence architecture - Chun, Yan; Kumar, Ashmit; Li, Xueyong (Frontiers in Plant Science, 2022)
Rice inflorescence is one of the major organs in determining grain yield. The genetic and molecular regulation on rice inflorescence architecture has been well investigated over the past years. In the present review, we described genes regulating rice inflorescence architecture based on their roles in meristem activity maintenance, meristem identity conversion and branch elongation. We also introduced the emerging regulatory pathways of phytohormones involved in rice inflorescence development. These studies show the intricacies and challenges of manipulating inflorescence architecture for rice yield improvement.